Effectiveness of Trastuzumab in Routine Clinical Practice: A Population-based Study of Patients with HER-2-positive Oesophageal, Gastroesophageal and Gastric Cancer. Issue 3 (March 2021) - Merchant, S.J.; Kong, W.; Gyawali, B.; Hanna, T.; Chung, W.; Nanji, S.; Patel, S.V.; Booth, C.M.
Abstract: Aims: In the pivotal Trastuzumab for Gastric Cancer (ToGA) trial, trastuzumab improved median survival in patients with advanced HER-2-positive gastric and gastroesophageal cancer from 11.1 to 13.8 months; however, its effectiveness in routine clinical practice has not been evaluated. Our objective was to evaluate the uptake and outcomes of trastuzumab in a population-based cohort of patients with oesophageal, gastroesophageal and gastric cancer in Ontario, Canada. Materials and methods: The Ontario Cancer Registry and linked treatment records were used to identify all patients with oesophageal, gastroesophageal and gastric cancer treated with trastuzumab during 2012–2017. Outcomes were analysed from the time of first trastuzumab cycle and included a primary outcome (survival) and secondary outcomes (uptake, delivery, 30-day hospital admission and 30-day mortality). Trends over the study period and survival were evaluated. Results: In total, 476 patients with oesophageal, gastroesophageal and gastric cancer received trastuzumab during the study period. The mean age was 62 years, 78% (370/476) were male, and 65% (312/476) had gastric cancer. The annual number of patients receiving trastuzumab increased over the study period (53 in 2012 and 101 in 2017). The median number of cycles of trastuzumab delivered was six. Thirty-day hospital admission and mortality rates were 17% and 4%, respectively. The median overall survival was 282 days (9.3 months). Conclusions: The median survival of patients treated with trastuzumab for advanced oesophageal, gastroesophageal and gastric cancer in routine practice is substantially less than that observed in the pivotal clinical trial. Studies of comparative effectiveness using real-world data offer insight into outcomes achieved in routine practice. Highlights: The uptake of trastuzumab in Ontario, Canada increased significantly over the study period. Median survival of patients treated with trastuzumab in routine practice is much less than observed in a landmark trial. Studies of comparative effectiveness using real world data offer insight into outcomes achieved in routine practice.